301 Health and behavioural outcomes associated with stress in malaysian police officers. (24th April 2018) - Retneswari, Masilamani; Bulgiba, Awang; Chinna, Karuthan; Darus, Azlan; Shathanapriya, Kandiben; Koh, David
Abstract : Introduction: Police officers are vulnerable to the stress provoking environment resulting in chronic police stress over time, with increasing susceptibility to diseases. Eventually, on-going stressors will drain energy and enthusiasm taking a toll on the worker's physical, mental (psychological) and behavioural health (lifestyle). The objective was to study the health and behavioural outcomes associated with stress among police officers in a Metropolitan Federal Territory of Malaysia – Kuala Lumpur. Methods: A cross-sectional study was conducted in two randomly selected police districts in Kuala Lumpur from 2012–2015. A total of 579 police officers from 2 headquarters and 11 police stations participated in this study. The 21-item Depression, Anxiety and Stress questionnaire was used. Multinomial logistic regression analyses were carried out. Result: The study reported that 40.3% police officers (95% CI: 55.0 to 64.3) had some level of stress; 6.4% (95% CI: 4.4 to 9.2) severe, 15.1% (95% CI: 11.9 to 19.0) moderate and 18.8% (95% CI: 15.3 to 22.8) mild. A police officer who reported mental illness had 6 times the odds of being severely stressed (aOR 5.83, 95% CI: 1.82 to 18.61) compared to one not mentally sick while a police officer who reported headache had nearly 3 times the odds of experiencing severe stress (aOR 2.91; 95% CI: 1.09 to 7.75) compared to one who reported no headache. A police officer who did not exercise or pray had 3.8 times odds (aOR 3.79, 95% CI: 1.65 to 8.75) and more than 5 times odds (aOR 5.15 (1.58, 16.85) of being severely stressed compared to an officer who exercised or prayed respectively. Discussion: Headache and mental illness were positively associated with police stress levels. Higher prevalence of stress justifies instituting peer counselling and stress reduction strategies while annual medical screening must be made compulsory for early detection of those with common diseases (hypertension and diabetes), frequent headache and mental diseases.